Management of complex colonic polyps in the English Bowel Cancer Screening Programme. Issue 12 (9th October 2013) - Lee, T. J. W.; Rees, C. J.; Nickerson, C.; Stebbing, J.; Abercrombie, J. F.; McNally, R. J. Q.; Rutter, M. D.
<x xml:space="preserve">Abstract</x> Background Large sessile or flat colonic polyps, defined as polyps at least 20 mm in size, are difficult to treat endoscopically and may harbour malignancy. The aim of this study was to describe their current management to provide insight into optimal management. Methods This retrospective observational study identified patients with large sessile or flat polyps detected in the English Bowel Cancer Screening Programme between 2006 and 2009. Initial therapeutic modality (surgical or endoscopic), subsequent management and outcomes were recorded. The main outcome measures analysed were: presence of malignancy, need for surgical treatment, complications, and residual or recurrent polyp at 12 months. Results In total, 557 large sessile or flat polyps with benign appearance or initial histology were identified in 557 patients. Some 436 (78·3 per cent) were initially managed endoscopically and 121 (21·7 per cent) were managed surgically from the outset. Seventy of those initially treated endoscopically subsequently required surgery owing to the presence of malignancy (19) or not being suitable for further endoscopic management (51). Residual or recurrent polyp was present at 12 months in 26 (6·0 per cent) of 436 patients managed endoscopically. There was wide variation between centres in the use of surgery as a primary therapy, ranging from 7 to 36 per cent. Endoscopic complications included bleeding in 13 patients (3·0 per cent) and perforation in two (0·5 per cent). Conclusion Management of large sessile or flat colonic polyps is safe and effective in the English Bowel Cancer Screening Programme. Wide variation in the use of surgery suggests a need for standardized management algorithms. Presented to a meeting of the British Society of Gastroenterology, Birmingham, UK, March 2011